Correctional Counseling and Treatment - Kratcoski, Peter C. (Springer, 2017)
Correctional Counseling and Treatment, Sixth Edition, is designed to provide information on the counseling and treatment methods currently being used in community and institutional corrections in the United States. The treatment methods and approaches that are most often used by criminal justice agencies are presented. The book is not comprehensive, since some treatment and counseling methods are not included. Those that appear to be the most useful to correctional personnel who provide supervision and counseling to those under supervision of justice agencies are examined. The treatment methods presented in the chapters and illustrated through information obtained from interviews with practitioners employed in criminal justice agencies appear to be those most relevant to the current practices of correctional agencies. In the Sixth Edition of Correctional Counseling and Treatment, all of the chapters are new and original, written by the author of the book or by invited authors. When the first edition of Correctional Counseling and Treatment was published in 1981, there was a debate over the purposes and effectiveness of correctional treatment. Kratcoski (1981, p.vii) noted, “A key element in the controversy that has arisen over the comparative effectiveness of various treatment programs is the fact that the purpose of correctional treatment has come to be regarded as prevention of recidivism.” This statement on the purposes of corrections was not accepted by everyone. Kratcoski, (1981, p.vii) noted “At that time, many of the persons employed in correctional agencies maintained that the goals of correctional treatment must be more broadly defined, and that successful treatment should be measured not only in terms of a lack of recidivism, but also by such progress as improved mental health, ability to perform adequately in a work situation, successful adjustment in the community, and appropriate handling of interpersonal relationships.”